Pengaruh Kinerja Keuangan Daerah terhadap Kemiskinan: - Kumba Digdowiseiso; Tino Rahardian; Lira Hartami (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The special autonomous regions experienced fluctuating changes in poverty rates throughout 2013-2021 which were influenced by various factors. This study aims to determine the effect of regional financial performance as measured through the ratio of independence, effectiveness ratio, and the ratio of compatibility of capital spending on poverty based on the Head Count Index (HCI-P0) in the four special autonomous provinces including Nanggroe Aceh Darussalam, Daerah Istimewa Yogyakarta, Papua Barat, dan Papua. Panel data as a combination of time series and the cross-section is obtained secondary from BPS and DJPK. This research method uses the panel data regression method and the Random Effect estimation model which was selected as the best estimator model. Data analysis in this study used the Eviews version 12 computer program. The results of the study stated that the financial independence ratio had a negative and significant effect on poverty. The ratio of effectiveness has a negative and insignificant effect on poverty, and the ratio of capital expenditure has a positive and significant effect. Simultaneously, the independent variable has a significant influence on the dependent variabel. Keywords: Regional financial independence ratio, PAD effectiveness ratio,regional expenditure compatibility ratio, poverty, special autonomy